The Ecoprophetism of Frank Herbert’s Dune - Smykowski, Mikołaj (Porównania, 2022)
The article is an attempt to read Frank Herbert’s science fiction novel “Dune” from the perspective of ecocriticism. The starting point for the discussion on the desert planet Arrakis and its specific waterless ecosystem created by the author on the level of the ecological fiction is to seek the ecomimetic analogies to the anthropocenic condition of the mid 20th century Earth. “Dune” as an ecoprophetic witness was hugely inspired by Herbert’s ecological and anthropological observations concerned with the native societies well adapted to lead a life on desert; it projects also the potential future scenarios of world deprived of water. Speculative character of Herbert’s “Dune” shows how thinking about the end of the anthropocene stimulates the anthropological imagination, which instead of the vision of planetary omnicide, may be helpful in projecting nonapocalyptic scenarios of the new beginning.